2021
DOI: 10.3390/math9182288
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Based 3D Object Reconstruction from Single 2D Image Using Variational Autoencoders

Abstract: In recent years, learning-based approaches for 3D reconstruction have gained much popularity due to their encouraging results. However, unlike 2D images, 3D cannot be represented in its canonical form to make it computationally lean and memory-efficient. Moreover, the generation of a 3D model directly from a single 2D image is even more challenging due to the limited details available from the image for 3D reconstruction. Existing learning-based techniques still lack the desired resolution, efficiency, and smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…It has also been shown that VAE models are capable of learning representations with disentangled factors (Higgins et al, 2016a) due to the isotropic Gaussian priors on the latent variable, the known power of the Bayesian models. The better performance of VAE compared to AE models has also been shown previously in other applications such as anomaly detection, object identification, and BCIs (Dai et al, 2019;Tahir et al, 2021;Zhou et al, 2021). As an additional point, comparing the results of VAE with SVAE, suggests the added value of supervised learning in training better models.…”
Section: Impact Of Variational Inference In Feature Learningsupporting
confidence: 72%
“…It has also been shown that VAE models are capable of learning representations with disentangled factors (Higgins et al, 2016a) due to the isotropic Gaussian priors on the latent variable, the known power of the Bayesian models. The better performance of VAE compared to AE models has also been shown previously in other applications such as anomaly detection, object identification, and BCIs (Dai et al, 2019;Tahir et al, 2021;Zhou et al, 2021). As an additional point, comparing the results of VAE with SVAE, suggests the added value of supervised learning in training better models.…”
Section: Impact Of Variational Inference In Feature Learningsupporting
confidence: 72%
“…However, it leads to the inability of the body model to model the human body in clothing. Therefore, nonparametric methods such as hulls [38], point clouds [39], triangular meshes [40], and voxel grids [41] were used for 3D human body reconstruction. They can predict shape representations directly from images.…”
Section: Human Body Reconstruction From Imagesmentioning
confidence: 99%
“…Several approaches focus on generating voxelized output representations. V3DOR [ 14 ] applied autoencoders and variational autoencoders to generate a smoother and high-resolution 3D model. The encoder aims to learn latent representation from the image and the decoder tries to obtain corresponding 3D voxels.…”
Section: Related Workmentioning
confidence: 99%